PENGARUH KOMPETENSI GURU DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISWA PAA MATA PELAJARAN EKONOMI BISNIS KELAS X ADMINISTRASI PERKANTORAN DI SEKOLAH MENENGAH KEJURUAN LAB BUSINESS SCHOOL KOTA TANGERANG TAHUN PELAJARAN 2018/2019 - Ana Muslichatun; Estu Niana Syamiya (Journal of Business Education and Social, 2020)
The purpose of this study was to determine the two variables, namely the presence or absence of the relationship between teacher competence and the learning environment with learning outcomes in the Vocational High School, Lab Business School, both partially and simultaneously. This research uses quantitative multiple regression method, with a sample of 93 students. The instrument of collecting data on teacher competence and the learning environment (independent variables) uses a questionnaire in the form of student personal data and learning outcomes (the dependent variable) uses a student's personal data questionnaire. The results of this study indicate that between teacher competency and learning environment only teacher competency variables significantly contribute to improving learning outcomes. it means that the higher the teacher's competency, the student learning outcomes will increase in business economics in the Vocational School Business School, Tangerang City School year 2018/2019.Keywords: teacher competence, learning environment and learning outcomes